An Analysis of Interpersonal Meaning of Modal Verbs in Abstracts from Scientific Papers: Case Study of Progress in Aerospace Sciences - Zhen Xu; Yi Zhang (Britain International for Academic Research (BIAR-Publisher), 2021)
The aims of this study are to explore the distribution features of modal verbs in abstracts from scientific papers, analyze the reasons for those features and figure out the role modal verbs play in achieving interpersonal meaning. The study has selected 60 abstracts randomly from Progress in Aerospace Sciences from 2015 to 2019 as research samples. It combines Halliday’s value of modality with Biber et al.’s two classifications to process modal verbs. The instruments adopted in this research are AntConc 3.2.4, manual sorting and SPSS Statistics 21. Based on the results, the study finds that: firstly, the overall occurrence of modal verbs in 60 abstracts is 59 times, among which low-value modal verbs are the most frequently distributed (74.6%), median-value modal verbs the second (22.0%) and high-value modal verbs the least (3.4%); secondly, the achievement of interpersonal meaning relies on value of modality, and when the value of modality is lower, a better degree of interpersonal meaning can be achieved; thirdly, high-value modal verbs achieve tough interpersonal meaning, median-value modal verbs achieve comfortable interpersonal meaning, and low-value modal verbs achieve harmonious interpersonal meaning.